Edukasi dan Penanaman Mangrove di Desa Taddan Kabupaten Sampang Jawa Timur - Syah, Achmad Fachruddin; Mubarok, Khamdi; Laksani, Mertiara Ratih Terry; Afifa, Fitria Hersiana; Purwandari, Umi (Jurnal Ilmiah Pangabdhi, 2024)
Mangroves have many benefits. However, not many people know and understand the benefits of mangroves. Therefore, this service aims to provide education and plant mangroves in Taddan Village, Sampang. The service carried out in July - November 2023 in Taddan Village, Camplong District, Sampang Regency. The tools and materials used in this service include mangroves, gloves, raffia rope and stakes. Mangrove education was carried out at the Taddan Village Hall, Sampang involving the Taddan Village community. Mangrove planting was carried out twice involving several parties including Forkopimcam, Camplong District, TNI-Polri personnel, Disaster Risk Reduction Forum (FPRB) Sampang Regency, Taddan Mangrove Conversation (TMC) Sampang, students of Trunojoyo Madura University (UTM) Bangkalan, and members of Saka Bhayangkara Sampang Quarter. This activity ran smoothly and successfully. The type of mangrove planted is Rhizopora stylosa with a total of 4000 seeds.It is hoped that planting mangrove tree seedlings can protect the coastline of Taddan Village from erosion and sea water abrasion while also protecting marine biota.